1996
DOI: 10.1007/bf01209651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dose-dependent enhancing effects of ?-ray irradiation on urethan-induced lung tumorigenesis in athymic nude (nu/nu) mice and euthymic (nu/+) littermates

Abstract: The role of immunological surveillance in carcinogenesis is still controversial. In our previous experiments, urethan-induced lung tumorigenesis in athymic (nu/nu) mice and euthymic (nu/+) littermates was examined, and it was concluded that immunosurveillance mediated by T cells could not be demonstrated. However, the reported enhancement of development of various tumors following ionizing radiation might be achieved through modulating the host immunological conditions. In the present experiment, nu/nu and lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It has been shown that g-radiation at low dose (2-4 Gy) promoted tumor cell infiltration with no pronounced impact on host immune function in nude mice (54). The ALDH high subpopulation accounted for 1.89% AE 0.85% of the total PC3M cells that initiated metastatic growth in the bone marrow of the irradiated immune-suppressive host mice, whereas unsorted PC3M cells homed to the bone marrow only when tumor cells were implanted by intracardiac injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that g-radiation at low dose (2-4 Gy) promoted tumor cell infiltration with no pronounced impact on host immune function in nude mice (54). The ALDH high subpopulation accounted for 1.89% AE 0.85% of the total PC3M cells that initiated metastatic growth in the bone marrow of the irradiated immune-suppressive host mice, whereas unsorted PC3M cells homed to the bone marrow only when tumor cells were implanted by intracardiac injection.…”
Section: Discussionmentioning
confidence: 99%
“…Athymic NMRI nude male mice ages 8 to 12 weeks (Taconic Europe) were used. For intravenous injection of tumor cells, mice were sublethally irradiated with two doses of 2 Gy administered 2 hours apart using a 137 Cs source at a dose rate of 1 Gy/minutes as described (54). Equal amounts of ALDH …”
Section: Mouse Model Of Prostate Cancer Distant Metastasesmentioning
confidence: 99%
“…Since the thymus is involved in the development of the majority of T cells (61, 62), these studies suggest that T cells do not significantly contribute to tumor immunosurveillance in the lung. Furthermore, nu/nu and nu/+ mice responded similarly to ionizing radiation treatment of urethane-induced lung cancer (64). …”
Section: The Role Of Nk Cells In Pulmonary Immunosurveillancementioning
confidence: 99%